First as “Politics,” then as “Art” - Ruda, Frank (Stasis, 2016)
The article investigates two contemporary propositions that it seeks to dismantle: 1. The proposition “everything is political” that it takes as one of the crucial implication of the concept of biopolitics. 2. The proposition “all art is political” that it takes to be a defense mechanism against the insight of the indefensibility of proposition 1. The article demonstrates how both propositions ultimately unfold from the mythic assumption of a givenness of politics and/or art and it concludes by suggesting that only a complete suspension of any kind of givenness might be a preparation for true politics or art to come. This preparation the article delineates as fatalist preparation.